2020
DOI: 10.1093/jxb/eraa168
|View full text |Cite
|
Sign up to set email alerts
|

Treat and trick: common regulation and manipulation of sugar transporters during sink establishment by the plant and the pathogen

Abstract: Abstract Sugar transport proteins are crucial for the coordinated allocation of sugars. In this Expert View we summarize recent key findings of the roles and regulation of sugar transporters in inter- and intracellular transport by focusing on applied approaches, demonstrating how sucrose transporter activity may alter source and sink dynamics and their identities. The plant itself alters its sugar transport activity in a developmentally dependent manner to eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…Furthermore, HvWRKY23, is activated upon PAMP-recognition by HvCERK1 and probably supports the resistance against the hemi-biotrophic head blight pathogen Fusarium graminearum (Karre et al, 2017;Karre et al, 2019). These examples support the hypothesis that the PAMP-dependent activation of the HvSTP13 promoter is a result of PTI signaling via WRKY TFs to combat the artificial sink that is generated by pathogens (Pommerrenig et al, 2020).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Furthermore, HvWRKY23, is activated upon PAMP-recognition by HvCERK1 and probably supports the resistance against the hemi-biotrophic head blight pathogen Fusarium graminearum (Karre et al, 2017;Karre et al, 2019). These examples support the hypothesis that the PAMP-dependent activation of the HvSTP13 promoter is a result of PTI signaling via WRKY TFs to combat the artificial sink that is generated by pathogens (Pommerrenig et al, 2020).…”
Section: Discussionmentioning
confidence: 53%
“…Botrytis cinerea, Blumeria graminis, Ustilago maydis, Pseudomonas syringae and various Xanthomonas species (Breia et al, 2020;Chen et al, 2010;Doidy et al, 2012;Sosso et al, 2019;Timilsina et al, 2020). In response, plants can activate the expression, or enhance the transport activity of SUTs or STPs to counter the pathogen-induced leakage of sugars (Bezrutczyk et al, 2018;Pommerrenig et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pith tissue harbored intermediate concentrations of both, monosaccharides and sucrose, as - in contrast to the storage parenchyma – it is not directly supplied with sucrose by the phloem. The application of the phloem mobile stain CFDA (Knoblauch et al, 2015; Mehdi et al, 2019; Pommerrenig et al, 2020) to source leaves allowed visualization of phloem fluxes into and within the sugar beet taproot and indicated that sucrose was transported in the taproot via the phloem in a similar manner. CFDA staining revealed organization of the phloem in vascular rings surrounding the pith ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the low sugar content in the plant apoplast might constrain their growth, pathogens utilize the sugar reservoirs of their host to convert the infection area into an artificial sink (Pommerrenig et al, 2020 ). SWEETs are well‐known targets that are exploited by diverse fungal and bacterial pathogens, for example Botrytis cinerea , Blumeria graminis , Ustilago maydis , Pseudomonas syringae , and various Xanthomonas species (Breia et al, 2020 ; Chen et al, 2010 ; Doidy et al, 2012 ; Sosso et al, 2019 ; Timilsina et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%